Pengaruh Sumber DAya Manusia dan Pemanfaatan Teknologi Informasi Akuntansi Terhadap Kinerja Pelaporan Keuangan Tahun 2010-2013 Pada Pemerintah Kota Surakarta - Budiarti, Zega; Nurlaela, Siti; Masitoh, Endang (Graduasi: Jurnal Bisnis & Ekonomi, 2015)
This study aimed to examine the effect of human resources and technology utilization of accounting information on the performance of financial reporting Surakarta municipal government.  Samples  were  employees  /  staff  DPPKA  in  the  Surakarta  municipal government  agencies.  Data  were  collected  by  taking  50  respondents  from  the  area  of the budget, treasury field, the field of assets and accounting and secretariat of the local government  areas  of  the  city  of  Surakarta.  Methods  of  data  collection  was  done  by using  purposive  sampling  judgment  through  the  survey.  Results  of  research  in  the formulation  of  hypothesis  H1  indicates  that  human  resources  are  not  significantly positive  effect  on  the  performance  of financial  reporting.  While the  results  of  a  second study  in  the  formulation  of  hypothesis  H2  suggests  that  the  existence of  significant influence  positively  the  use  of  information  technology  accounting  significant  positive effect  on  the  performance  of  financial  reporting.  Simultaneous  trials  and  research results  show  that  the  existence  of  significant  positive  effect  between human  resources and  technology  utilization  of  accounting  information  on  the  performance  of  financial reporting.